Tracking António Vieira's "Clavis Prophetarum": The St. Bonaventure, Franciscan Institute, Manuscript 28 - T. Valdez, Ana (2018)
The clavis Prophetarum or de Regno christi in terris consummato written by António Vieira, S.J. (1608–97) should be considered by scholars as one of the most important works of the seventeenth century. In it, Vieira introduces the reader to his interpretation of the theological concept of “Fifth Empire,” one that illustrates his imperial ideology, and consequently, a vision that might have influenced Portuguese imperial ideology during the reign of John IV of Portugal (r. 1640–56). This article introduces the recently discovered partial manuscript of the clavis Prophetarum found at St. Bonaventure University in the “Franciscan” Collection, ms. 28 and compares it with the two main existing manuscripts: biblioteca casanatense ms. 706 and arquivo Nacional da torre do tombo (aNtt), conselho Geral do santo ofício, ms. 122. This study will analyze more deeply how Vieira understood the concept of “invincible ignorance of God,” taking into consideration the differences in content in the St. Bonaventure, Franciscan Institute, ms. 28 compared to the other two manuscripts.